Visualizing Water Desaturation in Frozen Gas Diffusion Layers With Flow Field Segmentation via Synchrotron X-Ray Radiography - Zhang, Yuzhou; Anderson, Ryan; Zhu, Ning; Zhang, Lifeng (Frontiers in Energy Research, 2021)
Synchrotron X-ray tomography images were used to study dynamic, regional water transfer behavior in the gas diffusion layer (GDL) during thawing and desaturation processes. Initially saturated, frozen GDLs were thawed and desaturated with air in a serpentine gas flow channel. On-the-fly (OTF) high speed CT scans via synchrotron X-ray allowed the capture of consecutive water transfer inside the GDL under the cold start-up gas purging condition. Desaturation data of Sigracet 35AA GDLs with three superficial gas velocities (2.88–5.98 m/s) were selected for analysis. Multiple spatial segmentation levels based on the flow field geometry, including channel vs. rib, individual channels and ribs, and smaller sections in each channel and rib, were applied to the in-plane direction to study the GDL regional thawing and desaturation behaviors. Each segmentation volume had a similar desaturation pattern in general; however, water distribution and desaturation show heterogeneity over the GDL domain, as well as relation with factors including the flow field geometry, air traveling distance, and initial saturation level. These data from the segmentation analysis expand the knowledge of localized water transfer behavior during the cold start thawing process. These data can also provide valuable information for future cold start modeling and help in optimizing the PEM fuel cell flow field design.